Performance of a solar adsorption cooling and desalination system using aluminum fumarate and silica gel. (25th July 2021) - Elsheniti, Mahmoud Badawy; Rezk, Ahmed; Shaaban, Mohamed; Roshdy, Mohamed; Nagib, Yahia Mohamed; Elsamni, Osama.A.; Saha, Bidyut Baran
Highlights: Aluminum Fumarate is evaluated in a solar hybrid cooling and desalination system. The comparison with silica gel spotlights the net effects of a dynamic heat source. Interrelated effects of thermal and adsorption characteristics are critical issues. Aluminum Fumarate performance is affected negatively by the cumulative heat stored. Silica gel system is more responsive to changes in the initial heating temperature. Abstract: This paper numerically investigated the influence of adsorbent materials' thermal and adsorption characteristics on the overall performance of solar adsorption cooling cum desalination systems. A case study using an array of solar collectors was conducted to compare the emerging Aluminum Fumarate metal–organic framework (Al-Fum) with conventional silica gel (SG) under typical meteorological data at a selected site. Although the adsorption characteristics of Al-Fum outperforms SG at the material level, the former's low thermal characteristics increased the cumulative heat stored and limited the integrated-system performance. The low thermal diffusivity of Al-Fum slowed down the integrated system's response, providing that the average solar COPs of the SG-based system over different months were higher by 83%, 43%, and 22% at inlet chilled water temperatures of 15 °C, 20 °C, and 25 °C, respectively, and 1 mm fin spacing. However, the best specific cooling power of the AF-based system were higher than those of the SG-based system by − 16.6%, 16.8%, and 30.5% at these temperatures. Furthermore, the SG-based system was more negatively affected by reducing the heat storage initial temperature from 70 °C to 50 °C, but it attained COP and solar COP higher than those of the AF-based system by 14.9%–63%, respectively.